Two aquaporins, multiple ways of assembly - Jozefkowicz, Cintia (2016)
Protein oligomerization is a biological relevant event that may provide functional advantages to biological systems. The association of aquaporin (AQP) protomers to form hetero-oligomeric assemblies is a current challenging area of research. PIP1 and PIP2, members of the plant AQP subfamily named PIP (for plant plasma membrane intrinsic proteins), have been intensively studied in the recent years particularly due to their ability to hetero-oligomerize.